Morphometric Comparison of Kampong Chickens in Uepai District and Soropia District, Konawe Regency - Rusli Badaruddin; Muh. Rusdin; Natsir Sandiah; Sandi Trio Ramadhan; La Ode Nafiu; Muhammad Amrullah Pagala; La Ode Muh. Munadi (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2023)
Kampong chicken is the result of the domestication of the red jungle fowl (Red jungle fowl or Gallus gallus), raised by their ancestors for generations. It has spread to almost all parts of Indonesia. This study aims to identify and analyze the comparison of the quantitative characteristics of native chickens in the Uepai District and Soropia District, Konawe Regency. This research was conducted in Uepai District and Soropia District, Konawe Regency, from April to December 2022, using 400 kampong chickens aged 6-24 months consisting of 200 males and 200 females divided in the two study locations. This research shows that the quantitative characteristics of native chickens in the Uepai District have a higher average value than in the Soropia District, both for males and females. The coefficient of diversity value for body size of kampong chickens in Uepai District and Soropia District shows the medium (5≥) to high (15≥) category for both males and females.